"Obesity‐associated metabolic complications, the second wave of the tsunami" 14th Key Symposium. (19th October 2018) - Vidal‐Puig, A.; Enerback, S.
Abstract : Content List –14th Key Symposium ‐ "Metabolic Complications of Obesity" .